UMP Volunteer Squad extends assistance - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 22 January 2021 - Sympathise with the flood-ravaged houses and those affected by distress has prompted a total of 209 volunteers among the staff of Universiti Malaysia Pahang (UMP) to contribute to this humanitarian mission.